Pengelolaan Keragaman Sumber Daya Manusia dalam Organisasi - Febiana Ainun Ilmi; Coni Lestari; Afatar Rojab; Mu’alimin Mu’alimin (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Management of human resource (HR) diversity in organizations. HR diversity includes differences in race, ethnicity, gender, age, religion, disability, sexual orientation and cultural background. There are several challenges faced by organizations in managing HR diversity, including potential conflicts between employees, bias and discrimination, as well as difficulties in building cohesive teams. However, diversity also brings various opportunities, such as increased creativity and innovation, market expansion, and the ability to attract the best talent from various backgrounds. To maximize the benefits of HR diversity, organizations need to implement inclusive management strategies, such as diversity awareness training, anti-discrimination policies, and mentoring programs. In conclusion, effective HR diversity management not only helps organizations create a harmonious and productive work environment, but also provides a competitive advantage in an increasingly global and dynamic market.